A demographic study of salivary gland tumors - Manisha Aba Sardar; S M Ganvir; V K Hazarey (Wolters Kluwer Medknow Publications, 2018)
Background: Salivary gland lesions, especially the neoplastic lesions constitute a highly heterogeneous histopathologic group. Several studies have reported a significant difference in the global distribution of salivary gland tumors, but no formal study has been carried out in this part of the globe. Objectives: The objectives were: (1) retrieval of salivary gland tumors from the files of Department of Oral Pathology and Microbiology, Government Dental College and Hospital (GDC and H), Nagpur, to analyze the relative frequency of individual salivary gland tumors and (2) to correlate the various salivary gland tumors according to age, sex, location, and duration and compare the findings of this study with studies conducted in other countries. Materials and Methods: This is a retrospective study of all salivary gland tumors retrieved from the files of Department of Oral Pathology and Microbiology, GDC and H, Nagpur. Data thus collected archives were analyzed. Results: Out of total 75 cases, 29 pleomorphic adenoma, 8 basal cell adenoma, 16 mucoepidermoid carcinoma, 5 adenoid cystic carcinoma, 4 acinic cell carcinoma, 4 adenocarcinoma, 2 polymorphous low-grade adenocarcinoma, and single case each of cyst-adenoma, basal cell adenocarcinoma, epimyoepithelial carcinoma, salivary duct carcinoma, carcinoma in ex-pleomorphic adenoma, malignant myoepithelioma, and mucinous adenocarcinomas were reported. These cases were analyzed considering the parameters such as age, sex, location, duration, radiographic findings, and histopathological appearances. These were compared with studies conducted in other parts of the world. Conclusion: In conclusion, the data and results presented herein were similar to previously published reports in other countries and other areas of India and globe. However, some differences were observed, these differences can be attributed to racial factors, the pathology centers of sample collection and the duration of the studies.